1993
DOI: 10.1080/00288233.1993.10427487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-sowing herbicide and subsequent sward mass on survival, development, and production of autumn oversown Wana cocksfoot and Tahora white clover seedlings

Abstract: Although oversowing new grass and legume cultivars offers potential for development of hill country, the success of this technique is variable. The objective of this experiment was to assess the effect of pre-sowing herbicide and subsequent grazing management on autumn oversowing into dense, hill country pastures. Three herbicide treatments (paraquat, glyphosate, and unsprayed) and four spring grazing treatments (average cover of 500, 1000, 2000, and 3000 kg DMI ha) were compared. In general, 'Grasslands Wana'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As both herbicide spraying and pre-sowing defoliant techniques present problems for oversowing, more appropriate techniques are sought for hill pasture improvement (Barker and Dymock, 1993). A pastoral fallow was expected to reduce plant density and create a favourable environment for oversowing.…”
Section: Implications For Resowing Improved Forage Germplasmmentioning
confidence: 99%
See 2 more Smart Citations
“…As both herbicide spraying and pre-sowing defoliant techniques present problems for oversowing, more appropriate techniques are sought for hill pasture improvement (Barker and Dymock, 1993). A pastoral fallow was expected to reduce plant density and create a favourable environment for oversowing.…”
Section: Implications For Resowing Improved Forage Germplasmmentioning
confidence: 99%
“…McCallum et al (1991) showed that pastoral fallowing (or deferred grazing) improved perennial ryegrass contribution to yield by enhancing natural reseeding of this species, and increased pasture growth by 15-19% in the year following the fallow. Barker and Dymock (1993), reported on the management requirements for the successful establishment of one of the slowestablishing species, cocksfoot, and suggested that a pastoral fallow, rather than herbicide spraying, might bare the soil surface sufficiently, to allow germination and establishment of this slow-growing species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation